2016
DOI: 10.1016/j.laa.2016.03.033
|View full text |Cite
|
Sign up to set email alerts
|

Pseudo-inverses of difference matrices and their application to sparse signal approximation

Abstract: We derive new explicit expressions for the components of Moore-Penrose inverses of symmetric difference matrices. These generalized inverses are applied in a new regularization approach for scattered data interpolation based on partial differential equations. The columns of the Moore-Penrose inverse then serve as elements of a dictionary that allow a sparse signal approximation. In order to find a set of suitable data points for signal representation we apply the orthogonal patching pursuit (OMP) method.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…These formulations provide methods for the obtention of the Moore-Penrose inverse in the finite-dimensional case. We show that results appeared in [2,3,10,14], which were proved with different approaches, are particular cases of some of our formulations. In Example 3.4, we consider distance matrices D of weighted trees with all the weights being nonzero and with sum equal to zero.…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…These formulations provide methods for the obtention of the Moore-Penrose inverse in the finite-dimensional case. We show that results appeared in [2,3,10,14], which were proved with different approaches, are particular cases of some of our formulations. In Example 3.4, we consider distance matrices D of weighted trees with all the weights being nonzero and with sum equal to zero.…”
Section: Introductionmentioning
confidence: 60%
“…√ n e ∈ N(A), from Corollary 3.2(iii) we obtain [14,Theorem 2.1]. In [14], the authors first prove that A + αee t is nonsingular by showing that all its eigenvalues are nonzero.…”
Section: Formulations For Matricesmentioning
confidence: 99%
“…This has been used in [66] to relate linear PDE-based inpainting to sparsity concepts: Discrete Green's functions serve as atoms in a dictionary that gives a sparse representation of the inpainting solution. In the one-dimensional case, discrete analytic derivations are presented in [110].…”
Section: Relations To Other Methodsmentioning
confidence: 99%
“…Here, L † is sparse with respect to a 2-hop localized neighborhood on the graph. While closed-form expressions for the higher-order MPPs need to be derived on a case by case basis, it has been shown that the columns of L †2 C describe 4th order polynomials [30], from which it then naturally follows that the columns of L †2 C S T C = L † C S † C are cubic polynomials which are sparse with respect to the operator L 2 C ; accordingly, L †2 C L C = L † C describe quadratic polynomials, following a twofold degree-reduction. In addition L †2 C is sparse with respect to S C L 2 C , which possesses an extra vanishing moment through S C .…”
Section: General Circulant Graphsmentioning
confidence: 99%
“…4 (c) further illustrates the shape of the perturbation given by the columns of P −1 α at α = 4π/N , which exhibits a small support followed by approximate sparsity. In particular, the matrix P −1 α represents the difference between the MPPs of the simple cycle in (a) and the extended circulant in (b), and accordingly perturbs the functions underlying the former around its discontinuities, resulting in the constrained analysis representation 30 , as depicted in (b). Further, in Fig.…”
Section: The Generalized Graph Laplacianmentioning
confidence: 99%